Effectiveness of leuprolide acetate administered monthly compared to three-monthly in the treatment of central precocious puberty: evaluation at the end of treatment - Thaneetrakool, Thanaporn; Aroonparkmongkol, Suphab; Numsriskulrat, Nattakarn; Supornsilchai, Vichit; Wacharasindhu, Suttipong; Srilanchakon, Khomsak (Frontiers in Endocrinology, 2024)
Introduction: Gonadotropin-releasing hormone (GnRH) analogs are the standard treatment for central precocious puberty (CPP). Although there are numerous varieties of GnRH agonists, the effectiveness of 1-monthly compared with 3-monthly Leuprolide acetate is still restricted. The objective of this study was to evaluate the outcomes of CPP treatment with Leuprolide acetate at a 1-monthly dosage of 3.75 mg, in comparison to a dosage of 11.25 mg administered every 3 months.Method: This retrospective cohort study involved 143 girls diagnosed with CPP with 72 of them receiving the monthly treatment regimen and 71 receiving the 3-monthly treatment regimen.Anthropometric measurements were compared at the start and end of the therapy. The rates and level of LH suppression were assessed six months after therapy.Results: The regimen administered every 3 months showed more significant suppression of LH.The 3-monthly group showed lower actual height and degree of bone age advancement at the end of therapy. However, the predicted adult height (PAH) remained comparable in both groups.The 3-monthly treatment showed greater hormonal and growth suppression effects, but there was no significant difference in PAH between the two groups.